RF analog impairments modeling for communication systems simulation : application to OFDM-based transceivers - Smaini, Lydi, 1974- (Chichester, West Sussex, United Kingdom : Wiley, 2012)
"Logically ordered to follow the order of the blocks encountered along a receiver or a transmitter path in a communication platform, this book provides an introduction to system performance metrics, followed by topics on RF/Analog modeling, and simulation examples to support the modeling theory. With an emphasis on practical ways to apply the ideas presented, this book provides a comprehensive approach to unifying theory and practice in RF/Analog system modeling. Readers will be provided with practical RF/Analog system modeling knowledge and examples directly applicable to their on-going transceiver studies and simulations"--
"Covers the design aspects of the front end of transceivers, both receivers and transmitters"--
Machine generated contents note: 1 Chapter 1: Introduction to Communication System- On-Chip, RF analog front-end, OFDM modulation, and performance metrics 1.1 Communication System-on-Chip 1.1.1 Introduction 1.1.2 CMOS technology 1.1.3 Coexistence Issues 1.2 RF Analog Front-End Overview 1.2.1 Introduction 1.2.2 Super-heterodyne transceiver 1.2.3 Homodyne transceiver 1.2.4 Low-IF transceiver 1.2.5 Analog baseband Filter order vs. ADC dynamic range 1.2.6 Digital compensation of RF Analog Front-End imperfections 1.3 OFDM modulation 1.3.1 OFDM as a Multicarrier modulation 1.3.2 Fourier Transform and Orthogonal Subcarriers 1.3.3 Channel estimation and equalization in frequency domain 1.3.4 Pilot-tones 1.3.5 Guard interval 1.3.6 Windowed OFDM 1.3.7 Adaptive Transmission 1.3.8 OFDMA for Multiple Access 1.3.9 Scalable OFDMA 1.3.10 OFDM digital baseband architecture 1.3.11 OFDM-based standards 1.4 SNR, EVM, and Eb/N0 definitions and relationship 1.4.1 Bit error rate 1.4.2 SNR vs. EVM 1.4.3 SNR vs. Eb/N0 1.4.4 Complex baseband representation 2 Chapter 2: RF Analog impairments description and modeling 2.1 Introduction 2.2 Thermal Noise 2.2.1 Additive White Gaussian Noise 2.2.2 Noise Figure and Sensitivity 2.2.3 Cascaded noise voltage in IC design 2.2.4 AWGN in simulations 2.2.5 Flicker Noise and AWGN modeling 2.3 Oscillator Phase Noise 2.3.1 Description and Impact on the system 2.3.2 Phase Noise Modeling in Frequency Domain 2.3.3 Simulation in Temporal Domain 2.3.4 SNR limitation due to the phase noise 2.3.5 Impact of phase noise in OFDM 2.4 Sampling jitter 2.4.1 Jitter definitions 2.4.2 Sampling jitter and phase noise relationship 2.4.3 SNR limitation due to sampling jitter 2.4.4 Impact of sampling jitter in OFDM 2.4.5 Sampling jitter modeling 2.5 Carrier Frequency Offset 2.5.1 Description 2.5.2 Impact of Carrier Frequency Offset in OFDM 2.6 Sampling Frequency Offset 2.6.1 Description 2.6.2 Impact of Sampling Frequency Offset in OFDM 2.7 I & Q mismatch 2.7.1 Description 2.7.2 IQ mismatch modeling 2.7.3 SNR limitation due to IQ mismatch 2.7.4 Impact of IQ mismatch in OFDM 2.8 DAC/ADC quantization noise and clipping 2.8.1 SNR limitation due to the quantization noise and clipping level 2.8.2 Impact of converter clipping level in OFDM 2.8.3 DAC and ADC dynamic range in OFDM 2.8.4 DAC and ADC modeling 2.9 IP2 and IP3: 2nd and 3rd Order non-linearities 2.9.1 Harmonics (Single-tone test) 2.9.2 Intermodulation Distortion (Two-tone test) 2.9.3 Receiver performance degradation due to the non-linearities 3 Chapter 3: Simulation of the RF Analog impairments impact on real OFDM-based transceivers performance 3.1 Introduction 3.2 WLAN and mobile WIMAX PHY overview 3.2.1 WLAN: Standard IEEE 802.11a/g 3.2.2 Mobile WiMAX: Standard IEEE 802.16e 3.3 Simulation bench overview 3.3.1 WiFi and WiMAX OFDM transceiver modeling 3.3.2 EVM estimation as performance metric 3.3.3 EVM vs. SNR simulations in AWGN channel 3.4 WiFi OFDM and mobile WiMAX signals PAPR 3.5 Transmitter impairments simulation 3.5.1 Introduction 3.5.2 DAC clipping and resolution 3.5.3 I & Q mismatch 3.5.4 RF oscillator phase noise 3.5.5 Power amplifier distortion 3.5.6 Transmitter complete simulation 3.6 Receiver impairments simulation 3.6.1 Introduction 3.6.2 Carrier Frequency Offset 3.6.3 Sampling Frequency Offset 3.6.4 Linearity: IIP2 and IIP3 3.6.5 I & Q mismatch 3.6.6 RF oscillator phase noise and reciprocal mixing 3.6.7 Sampling jitter 3.6.8 ADC clipping and resolution 3.6.9 Receiver complete simulation 3.7 Adaptive modulation illustration 3.8 Summary 4 Chapter 4: Digital Compensation of RF analog Impairments 4.1 Introduction 4.2 Carrier Frequency Offset Estimation and Correction 4.2.1 CFO estimation principle 4.2.2 CFO estimation in time domain 4.2.3 CFO estimation in frequency domain 4.2.4 CFO correction 4.3 Sampling Frequency Offset Estimation and Correction 4.3.1 SFO estimation principle 4.3.2 SFO estimation 4.3.3 SFO correction 4.3.4 Joint SFO and CFO estimation 4.4 IQ mismatch estimation and correction 4.4.1 Principle 4.4.2 Effect of the channel 4.4.3 Simulation results 4.5 Power Amplifier Linearization 4.5.1 Digital Predistortion Principle 4.5.2 Memory polynomial predistortion 4.5.3 Polynomial coefficients computation 4.5.4 Simulation results 4.6 Summary.
BIBINDX
Print version record and CIP data provided by publisher.
Keywords: Radio -- Transmitter-receivers -- Simulation methods; Electromagnetic interference; Signal integrity (Electronics); Telecommunication systems -- Simulation methods; Orthogonal frequency division multiplexing; Radio -- Transmitter-receivers -- Simulation methods; Electromagnetic interference; Signal integrity (Electronics); Telecommunication systems -- Simulation methods; Orthogonal frequency division multiplexing; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- General; Radio / Transmitter-receivers / Simulation methods; Electromagnetic interference; Signal integrity (Electronics); Telecommunication systems / Simulation methods; Orthogonal frequency division multiplexing; Electronic books; Electronic books